Proyecto de mejora de un gasocentro vía la implementación de una estación de combustibles líquidos - Campero Longa, Enrique Javier (2019)
This report will summarize the process that was carried out in order to decide the most appropriate solution, the proposal development to expand the company's business lines, and the execution, construction, assembly and commissioning of the facilities to generate the supply of liquid fuels that resulted in the increase in sales that grew from an average of 400 000 soles to more than 1 000 000 soles per month and will also show how timely this decision was due to external events that affected the business operation. Likewise, it can be concluded that for the growth of the company and the business group to which it belongs, this decision generated a broader knowledge of the hydrocarbons sector that could be replicated in other undertakings that it carried out.